Predicting factors for social oocyte cryopreservation intention among unmarried Korean women - Lee, Sung Hee; Baek, Ji Woo; Lee, Yeong Ju; Choi, Ki Hoon; Choi, Yu Jin; Ha, Si Eun; Choi, Hyo Won; Kim, Jung A (Edelweiss Applied Science and Technology, 2024)
In 2023, the average age of Korean women for the first marriage and giving birth was reported to 31.45 and 33.6, respectively. Due to the late marriage, the number of patients undergoing infertility treatment per 100,000 in Korea increased by 16.9% over the past five years to 27.3. Recently, interest in social oocyte cryopreservation (SOC) has been growing in Korea as a strategy to address the low birth rate. This study is descriptive research to determine the influence of unmarried women’s knowledge of fertility preservation, tendency toward late marriage, and awareness of fertility preservation on intention to SOC. This study aims to identify predictors of unmarried women’s intention to SOC. Data were collected from July 20 to 26, 2024, through a online self-reported survey from unmarried women in their 20s to 40s. 234 copies were collected, but 211 copies were used for the analysis after excluding 23 insincere responses. The data were analyzed using descriptive statistical analysis and logistic regression analysis using the SPSS/PC 29.0 program. In this study, 41.7% of unmarried women intended to SOC, while 58.3% did not. In addition, the intention to SOC was higher when they wanted children (p=.041, exp(B)=2.35), were aware of SOC (p=.015, exp(B)=2.98), and had a high awareness of fertility preservation (p<0.001, exp(B)=1.47). But the higher the tendency to marry late (p=.044, exp(B)=.92), the lower the intention to SOC. The findings can serve as foundational data to increase social awareness of SOC for unmarried women and to help develop supportive policies.